TOWARDS A NEW, DIGNIFIED INDONESIA: A REFLECTION ON THE HISTORICAL JOURNEY OF ISLAM IN CONTEMPORARY INDONESIA - Zalmesi Zulmar (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This article analyzes the historical journey of Islam in Indonesia in the contemporary era through four main phases: the role of Islamic figures in the establishment of the Unitary State of the Republic of Indonesia in 1945 the political activities of Muslims in the period 1950–1966 the dynamics of the relationship between the state and Islam during the New Order era, which was marked by depoliticization and structural integration; and the significant changes brought about by the 1998 Reformation era to Indonesia's socio-political configuration. This study uses a descriptive qualitative approach based on literature review, utilizing national scientific sources, historical archives, and contemporary academic works. The results of the study show that Muslims have played a consistent role in shaping national identity, political transformation, and strengthening the foundations of democracy in Indonesia. The dynamics of state-religion interactions in each period confirm that the contribution of Muslims is not only political, but also intellectual and cultural, making them an integral part of the process towards a more democratic and dignified Indonesia.